Science Laboratory Management at State Middle School 8 Lubuklinggau Using the Cipp Model - Dina Puspita Sari; Linda Nurfalah; Sapira; Maharani Khitimah, Etika; Sulistiyono (Journal of Practice Learning and Educational Development, 2026)
This study aims to evaluate the management of the science laboratory at SMP Negeri 8 Lubuklinggau using the CIPP (Context, Input, Process, Product) evaluation model. The study employed an evaluative approach with descriptive qualitative methods. Subjects included the principal, science teachers, and laboratory administrators. Data collection techniques included observation, interviews, and documentation studies. The results indicate that, from a contextual perspective, the science laboratory meets learning needs and is supported by school policy, although laboratory planning has not been systematically developed. From an input perspective, basic infrastructure is available, but there are still limitations in tools and laboratory materials, and the lack of dedicated laboratory staff. From a process perspective, practical activities have been carried out but not routinely, and laboratory administration and the implementation of occupational safety and health (K3) are not yet optimal. From a product perspective, the utilization of the science laboratory has a positive impact on student conceptual understanding and learning motivation. Overall, the management of the science laboratory is considered quite good, but still requires improvement, particularly in planning, procurement of facilities, and operational management to ensure optimal and sustainable laboratory function.